2003
DOI: 10.1097/00126334-200312010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Once-Weekly Epoetin Alfa Dosing Is as Effective as Three Times–Weekly Dosing in Increasing Hemoglobin Levels and Is Associated With Improved Quality of Life in Anemic HIV-Infected Patients

Abstract: QW dosing of epoetin alfa is as effective as TIW dosing in increasing Hb levels, which was associated with improved QOL in anemic HIV-positive patients. QW dosing should also offer added convenience for patients and caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 28 publications
1
36
0
1
Order By: Relevance
“…Although the increased BP often parallels the rise in hematocrit, studies in both iron-deficient rodents (32) and humans (33) have conclusively demonstrated that these two events are not causally linked and that rhEPO acts directly on the vasculature. To determine whether the pressor action of rhEPO is mediated through the hematopoietic (EPOR) 2 or the tissue-protective EPOR-␤c receptor, we treated rats with rhEPO or CEPO while monitoring systolic BP plethysmographically via tail cuff. Chronic administration of rhEPO at either low (1.2 g͞kg of bw twice weekly) or high (40 g͞kg of bw three times weekly) doses was associated with significant and comparable increases in systolic BP of 12 Ϯ 3% (low dose) and 5 Ϯ 2% (high dose) of baseline (118 Ϯ 6.1 mmHg; 1 mmHg ϭ 133 Pa), respectively (P Ͻ 0.05 vs. saline and P Ͻ 0.01 vs. CEPO).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the increased BP often parallels the rise in hematocrit, studies in both iron-deficient rodents (32) and humans (33) have conclusively demonstrated that these two events are not causally linked and that rhEPO acts directly on the vasculature. To determine whether the pressor action of rhEPO is mediated through the hematopoietic (EPOR) 2 or the tissue-protective EPOR-␤c receptor, we treated rats with rhEPO or CEPO while monitoring systolic BP plethysmographically via tail cuff. Chronic administration of rhEPO at either low (1.2 g͞kg of bw twice weekly) or high (40 g͞kg of bw three times weekly) doses was associated with significant and comparable increases in systolic BP of 12 Ϯ 3% (low dose) and 5 Ϯ 2% (high dose) of baseline (118 Ϯ 6.1 mmHg; 1 mmHg ϭ 133 Pa), respectively (P Ͻ 0.05 vs. saline and P Ͻ 0.01 vs. CEPO).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent work has identified an additional receptor comprised of the EPOR and the ␤c receptor (CD131) subunit, the latter also used for granulocyte͞macrophage colony-stimulating factor (GM-CSF), IL-3, and IL-5 signaling (29). CEPO is therefore a useful ligand to distinguish between effects mediated by the hematopoietic (EPOR) 2 and cytoprotective EPOR-␤c receptors. The data described here, obtained after doses reasonably anticipated for future study of tissue protection in humans, suggest that stimulation of human multipotent hematopoietic colonies and rat platelets, as well as E-and P-selectin (and possibly PAI-1) up-regulation are mediated by the (EPOR) 2 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations